2006
DOI: 10.1186/1471-2156-7-10
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationship and diversity in a sesame (Sesamum indicum L.) germplasm collection using amplified fragment length polymorphism (AFLP)

Abstract: BackgroundSesame is an important oil crop in tropical and subtropical areas. Despite its nutritional value and historic and cultural importance, the research on sesame has been scarce, particularly as far as its genetic diversity is concerned. The aims of the present study were to clarify genetic relationships among 32 sesame accessions from the Venezuelan Germplasm Collection, which represents genotypes from five diversity centres (India, Africa, China-Korea-Japan, Central Asia and Western Asia), and to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
3
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(72 citation statements)
references
References 35 publications
6
61
3
2
Order By: Relevance
“…The majority of the variance occurring among the individuals accounted for 57 per cent of the total variation, and seven per cent of the variation was attributed to differences among the countries of origin (Appendix 6). Similar results were also described, where differences among geographical regions were represented only by five per cent of the total variation in sesame lines (Laurentin et al, 2006;Woldesenbet et al, 2015). In order to resolve the relationships among the entries, a NJ tree based on pairwise population matrix of Nei unbiased genetic distance values was generated ( Figure 1).…”
Section: Genetic Diversity and Germplasm Structuresupporting
confidence: 71%
“…The majority of the variance occurring among the individuals accounted for 57 per cent of the total variation, and seven per cent of the variation was attributed to differences among the countries of origin (Appendix 6). Similar results were also described, where differences among geographical regions were represented only by five per cent of the total variation in sesame lines (Laurentin et al, 2006;Woldesenbet et al, 2015). In order to resolve the relationships among the entries, a NJ tree based on pairwise population matrix of Nei unbiased genetic distance values was generated ( Figure 1).…”
Section: Genetic Diversity and Germplasm Structuresupporting
confidence: 71%
“…Isshiki and Umezaki (1997) reported small variation among 68 accessions of cultivated sesame using isozymes. Laurentin and Karlovsky (2006) reported on a very low genetic relationship and diversity (0.14-0.21) in 32 sesame germplasm collections using amplified fragment length polymorphism (AFLP). A microsatellite ISSR-based study of sesame from Korea and other countries revealed a low level of polymorphism in that particular marker and genetic distance ranged from 0 to 0.255 (Kim et al 2002).…”
Section: Discussionmentioning
confidence: 98%
“…To assay whether the 112 polymorphic SSR markers were segregated independently or not, LD analysis was conducted according to the dedicated procedure of the TASSEL software [49]. Both D ′ and r 2 were used for quantifying LD values [74], [75].…”
Section: Methodsmentioning
confidence: 99%